(untitled) (International Journal of Engineering and Computer Science, 2017)
We propose new algorithm to hide data inside image using Steganography and Encryption. The proposed algorithm uses binary codes and pixels inside an image. The file is converted to binary codes to maximize the storage of data inside the image. By applying the proposed algorithm, a system called STEGA IMAGE is developed. The system is then tested to see the viability of the proposed algorithm. Various sizes of data are stored inside the image, Depends upon the pixels of the Carrier Image.